Percutaneous Intra-articular Chevron Osteotomy (PeICO): clinical and radiographic outcomes - Brandão Magalhães, João Murilo; Ferreira, Gabriel Ferraz; Sevilla, Davy; Barbosa, Raul Carlos; Braga, Bruno Maciel; Zambelli , Roberto; Nunes, Gustavo Araújo (Journal of the Foot & Ankle, 2023)
Objective: Hallux valgus (HV) is a complex deformity with several surgical treatments described, and percutaneous methods are increasingly used. The objective of the study was to evaluate the clinical and radiographic outcomes of patients with mild or moderate HV submitted to surgical treatment using the Percutaneous Intra-articular Chevron Osteotomy (PeICO) technique. Methods: A retrospective case series of 15 patients (18 feet) diagnosed with mild or moderate HV submitted to surgical treatment by the PeICO technique. Clinical variables analyzed were pain using the visual analog scale (VAS), function using the American Orthopaedic Foot and Ankle Society (AOFAS), personal satisfaction, and surgical complications. Radiographic parameters measured in the pre-and postoperative were hallux valgus angle (HAV), intermetatarsal angle (AIM), sesamoids position, and osteotomy consolidation. Results: The mean follow-up time was 14 months. There was an improvement in clinical outcomes, with a mean increase in AOFAS of 31.1 and a reduction of 5.6 in VAS, with significant differences between the pre-and postoperative values (p < 0.001). There was also a significant radiographic correction in the HVA and AIM (p < 0.001). The most common complication observed was screw removal in three cases (16.6%). Conclusion: The PeICO technique presented excellent radiographic correction, clinical improvement, high personal satisfaction, and low complication rate when used for the surgical treatment of mild or moderate hallux valgus. Level of Evidence IV; Cases series; Retrospective Study.